UMP driver schedulling reminder system - Nor Hamizah, Ahmad Azmi (2012)
The thesis describes research into solving the (JPPH) Jabatan Pembangunan Dan Pengurusan Harta driver scheduling reminder problems. Currently, driver scheduling reminder at (JPPH) Jabatan Pembangunan Dan Pengurusan Harta is done manually. The applicant needs to get the booking form from Jabatan Hal Ehwal Pelajar & Alumni or (JPPH), and employees at (JPPH) will manage the vehicle booking request made by the applicant, from that employees will arranged scheduling for drivers and vehicles manually before publishing the schedule on the office board . The drivers need to commute every day to update and confirm the tasks schedule before doing their tasks. The manual process of arranged scheduling is a slow and tedious work, usually done by those with knowledge of resources and constraints for specific organization. Manual process also faced some problem such as use a lot of time, paper, money and energy. JPPH also have conflict to manage the scheduling accurately, like when the paper is torn or lost The main aims Driver Scheduling Reminder System is to help administrator at JPPH arranged their driver and vehicle scheduling easier and sends scheduling reminder to driver through email and Short Message Service (SMS) every day, This system also; to enhanced and provide an easy way for create a new drivers schedule. The System users are drivers and employees that are involved in making a schedule and sends tasks reminder for JPPH drivers. Rapid Application Development method is use from beginning to the end of development of this proposed system. This system, with simple application and user-friendly interface will help the employees who making the arranged scheduling at JPPH to do the arranged scheduling process easily and give drivers easier way to confirm their driving task. Most of the objective set-out in this project was successfully achieved.